How do you solve 4(3n - 2) (4n + 1) = 0?

1 Answer

n=2/3 and -1/4

Explanation:

You can interpret the equation this way:
The product is 0 when you multiply the three factors 4, (3n-2), and (4n+1). Therefore, either of the three factors must be zero to make the statement true.

you can see it this way
(4)\cdot(0)\cdot(4n+1)=0
or
(4)\cdot(3n-2)\cdot(0)=0
or
(4)\cdot(0)\cdot(0)=0

Which means to say, that the factor (3n-2) and/or (4n+1) should be zero.

So,
3n-2=0
=>3n=2
=>n=2/3

Also,
4n+1=0
=>4n=-1
=>n=-1/4

Therefore, n=2/3 and -1/4

Another method is to expand the whole expression and perform long division. you should arrive with the same answer.